Symbolic Governance? Independent Commissioners And Institutional Ownership On Tax Avoidance In State-Owned Enterprises - Sakti, Maharani Evelyna Putri; Nuswantara, Dian Anita; Runn, Pharat (Universitas Riau Kepulauan, 2025)
Tax avoidance remains a persistent challenge in emerging economies, particularly within State-Owned Enterprises (SOEs) that are expected to serve both commercial and public functions. This study investigates the influence of independent commissioners and institutional ownership on tax avoidance among SOEs listed on the Indonesia Stock Exchange (IDX) during the 2015–2023 period. The research adopts a quantitative approach with an inferential design, utilizing secondary data derived from the annual reports of 23 SOEs that met the sample criteria, resulting in 207 firm-year observations. Tax avoidance is measured using the Effective Tax Rate (ETR). The analytical method employed is Generalized Least Squares (GLS) regression, with the Random Effect Model (REM) selected based on Chow, Hausman, and Lagrange Multiplier tests. Data processing was conducted using STATA version 17, and the model's validity was tested through classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation. The results reveal that the proportion of independent commissioners has no significant effect on tax avoidance, while institutional ownership is negatively associated with ETR, indicating a positive effect on tax avoidance. These findings suggest that institutional ownership in SOEs may not effectively function as a governance mechanism due to political interference and agency conflicts. This study contributes to the corporate governance literature by offering empirical insights into the symbolic nature of governance structures in government-owned firms, particularly in the context of developing countries.